Detection of Unculturable Bacteria in Periodontal Health and Disease by PCR - Harper-Owen, R. (American Society for Microbiology, 1999)
Recently developed molecular methods have made it possible to characterize mixed microflora in their entirety, including the substantial numbers of bacteria which do not grow on artificial culture media. In a previous study, molecular analysis of the microflora associated with acute oral infections resulted in the identification of three phylotypes, PUS3.42, PUS9.170, and PUS9.180, representing as-yet-uncultured organisms. The aim of this study was to design and validate specific PCR primers for these phylotypes and to determine their incidences in samples collected from healthy and diseased periodontal tissues. Two specific reverse primers were devised for each phylotype, and these were used in duplex PCRs with universal forward and reverse primers. All three phylotypes were detected in periodontal sites; PUS9.170, related to oral asaccharolytic Eubacterium spp., was significantly associated with disease. This study demonstrates the possibility of using unculturable, and therefore uncharacterized, organisms as markers of disease.